2007
DOI: 10.1167/iovs.06-1150
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Femtosecond Laser Keratotomy Results in Isolated Stromal Injury and Favorable Wound-Healing Response

Abstract: Isolated stromal injury using an fs laser avoids epithelial injury and is associated with a favorable wound-healing response preserving corneal transparency. Thus, fs laser keratotomy is a highly selective laser treatment that can be useful for the treatment of refractive errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 44 publications
5
34
0
Order By: Relevance
“…Both femtosecond laser (first set of experiments) and LASIK (second set of experiments) techniques are associated with a proper wound-healing response preserving corneal transparency and not eliciting differentiation of keratocytes into fibroblasts [53]. Whether or not perfect optic transparency is achieved, obtaining a cell source that can be committed to keratocytes and able to repopulate and regenerate cornea-like tissue, as found in our study, could be very valuable in situations compromising the stroma, such as corneal thinning diseases, traumatic loss of stromal tissue, or corneal damage after infection or immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both femtosecond laser (first set of experiments) and LASIK (second set of experiments) techniques are associated with a proper wound-healing response preserving corneal transparency and not eliciting differentiation of keratocytes into fibroblasts [53]. Whether or not perfect optic transparency is achieved, obtaining a cell source that can be committed to keratocytes and able to repopulate and regenerate cornea-like tissue, as found in our study, could be very valuable in situations compromising the stroma, such as corneal thinning diseases, traumatic loss of stromal tissue, or corneal damage after infection or immune response.…”
Section: Discussionmentioning
confidence: 99%
“…This model produces a favorable wound-healing response, preventing excessive inflammatory reaction [53], which may distort the stem cell behavior. The cornea is an external tissue suitable to stem cell therapy because of its easy accessibility by surgical maneuvers.…”
Section: Discussionmentioning
confidence: 99%
“…The findings by Zohdy et al that LIOB can be controlled to be thermally noninvasive, with a measurable temperature increase of less than 1°C in the vicinity of a femtosecond laser-generated bubble, are congruent with our observations of no discernable thermal collateral damage. Wang et al [8] using multiphoton microscopy technology and Meltendorf et al [9] in light and electron microscopy also found highly circumscribed injury to the corneal stroma limited to the target zone.…”
Section: Discussionmentioning
confidence: 97%
“…The high energy generates tiny plasmas and vaporizes tissue at a given plane while leaving surrounding tissue intact. Using this approach, stromal photodisruption can be achieved without injuring the anterior and posterior epithelial layers of the cornea [6,7]. This "intrastromal laser surgery" is attractive because of its potential for minimizing wound-healing responses as well as reducing the risk of postoperative infection [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, stromal photodisruption can be achieved without injuring the anterior and posterior epithelial layers of the cornea [6,7]. This "intrastromal laser surgery" is attractive because of its potential for minimizing wound-healing responses as well as reducing the risk of postoperative infection [7,8]. Previous experimental clinical studies have provided first evidence that the desired effect of central corneal thinning can be achieved by intrastromal photodisruption using pico-or femtosecond lasers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%